ANALISA CORPORATE CREDIBILITY TERHADAP PURCHASE INTENTION TELKOMSEL 4G-LTE DENGAN ATTITUDE TOWARD THE ADVERTISING DAN ATTITUDE TOWARD THE BRAND SEBAGAI VARIABEL INTERVENING - Ayu Nirmala Putri (Jurnal Manajemen Pemasaran, 2015)
This study was conducted to determine the effect of the Purchase Intention Corporate Credibility Telkomsel 4G - LTE with Attitude toward the Advertising and Attitude toward the Brand as a variable intervening.Sampel research is 100 respondents Telkomsel users who have seen an ad Telkomsel 4G - LTE and has a device which supports 4G - LTE network , living in the West and East Surabaya Surabaya . This study uses SEM analysis techniques to yield significant results for each variable used